Analisis Framing Berita Penangkapan Gubernur Riau Annas Maamun di Surat Kabar Riau Pos dan Tribun Pekanbaru - Al Sukri; Chelsy Yesicha (Program Studi Ilmu Komunikasi FISIP Universitas Syiah Kuala, 2017)
The arrest of Riau Governor, Annas Maamun on September 25th2014 by the Corruption Eradication Commission (KPK) in Jakarta, has attracted the attention of the mass media because of its news value. In addition to his controversial figure with a seven-month term, he was the third consecutive Governor to stumble over a case of corruption in Riau. This research uses constructive paradigm using Framing Pan and Kosicki analysis method with the assumption that each news article has a frame which functions as a center of the organizational idea. Riau Pos and Tribun Pekanbaru have their own views to frame their news. They are the biggest local media which are parts of the biggest news networks in Indonesia. The results show that the two media did not deny the urgency of the event but they have their own point of view in addressing the issue. Riau Pos tends to uphold the principle of editorial policy by maintaining the honor of Riau and Tribun Pekanbaru has the principle of raising public awareness to keep Riau.